Development of a Clinical Database for the Implant and Follow-up of Cardioverter Systems. - Benedek ZM; Furman S (Pacing & Clinical Electrophysiology, 1988)
The purpose of a clinical database in AICD follow-up is twofold: to follow the evolution (1) of the patient and (2) of the implanted hardware. The pacemaker implant is performed the same day, whereas the implant of a complete AICD system can span over several days or even weeks. Therefore the first design criteria for the database is to clearly identify a single procedure. AICDs require the use of several leads 0/different types and functions and each lead has to be followed independently. There/ore the second design criteria is to establish a continuous history for each device implanted. To accomplish this the following method has been devised. The implant patient has a single demographic form and for each new procedure a 'Purpose of Procedure' form is filled out, which is identified by the date the form was initiated and by the patient's ID number. There are separate forms for the defibrillator and for three types of leads (transvenous, epicardial sensing and patch leads). For each hardware implanted a specific form is filled out and keyed to the 'Purpose of Procedure' form. Consequently the patient is monitored through the sequence of 'Purpose of Procedure' forms, the defibrillator and the leads through the hardware forms. Stimulation and sensing threshold measurements are part of the respective hardware forms but the induced tachycardia measurements are separate. At present 56 AICDs have been followed in the database.